Uma mãe, um mestiço, um epilético e uma prostituta: as irônicas interidentidades em O esplendor de Portugal (1997), de António Lobo Antunes - Cruz, Kairo Lazarini da (2024)
This work aims to analyze the novel O Esplendor de Portugal (1997), by António Lobo Antunes, from a post-colonial perspective. Although this starting point is not exactly new, I hope that my reading proposal of the novel will enrich its critical reception with new points of view and highlight the importance of this approach in contemporary discussions about Portuguese identity. The dissertation is developed through two interconnected lines of analysis. Firstly, it’s based on Boaventura de Sousa Santos' (2003) concept of “interidentity”, which suggests that the self-representation of the Portuguese colonizer creates a disjunction between the subject and object of colonial representation. I examine the way in which the characters Isilda, Carlos, Rui and Clarisse, Portuguese settlers in Africa in the context of the historical end of colonialism and the subsequent Angolan Civil War (1975-2002), evoke geographic displacement and family breakdown as paradigmatic examples of this concept. Secondly, I argue that the notion of inter-identity allows to formulate an ironic subversion of symbolic systems that represent the colonial ethos of the Portuguese empire. From this point of view, the family microcosm of this novel can function as a model for a sustained critique of the notion of “Portugal's splendor” popularized by the official historiography of the Portuguese Estado Novo.